The Primary Structure of the Inhibitor of Tissue Plasminogen Activator Found in the Seeds of Erythrina caffra - Joubert, F J; Dowdle, E B D (Thrombosis and Haemostasis, 1987)
Trypsin and tissue plasminogen activator inhibitor DE-3 from Erythrina caffra contains 172 amino acids, including 4 half-cystine residues, and resembles the Kunitz-type inhibitors. Limited hydrolysis of DE-3 with trypsin at pH 3.2 produced two fragments, FI and F2, containing 63 and 109 amino acids, respectively. Amino-terminal sequence studies showed that FI was the N-terminal and that F2 was the C-terminal fragment. The complete amino acid sequence of the fragments were then determined on peptides produced by enzymatic digestion with trypsin. The sequence of trypsin and tissue plasminogen activator inhibitor DE-3 from E. caffra seeds shows a high degree of homology to that of trypsin and tissue plasminogen activator inhibitor DE-3 from E. latissima seeds and revealed only four amino acids which were replaced.
Keywords: Erythrina caffra; Trypsin and tissue plasminogen activator inhibitor; Amino acid sequence